Pengembangan LKPD Fisika Berbasis Saintifik untuk Meningkatkan Motivasi dan Hasil Belajar Siswa - Sayyidatur Rafifah; Endang Lovisia; Ahmad Amin; Sulitiyono Sulitiyono; Ovilia Putri Utami Gumay (Science and Physics Education Journal (SPEJ), 2025)
Abstract: This research aims to develop a scientific-based Physics Student Worksheet (LKPD) on Newton’s Laws to improve the learning motivation and outcomes of Grade X students at MA Mifftahussalam Megang Sakti. The development method employed was the 4D model (Define, Design, Develop, Disseminate), which consists of defining needs, designing the product, developing through validation and trials, and conducting limited dissemination. The subjects of this study were 17 students of Grade X, while the research instruments included expert validation sheets, learning motivation questionnaires, as well as pretest and posttest items. Validation carried out by material, media, and language experts indicated that the developed LKPD met the “very good” category. Limited and field trials revealed that students’ motivation increased to the “very good” category with an average percentage above 85%. Students’ learning outcomes also improved significantly, as reflected in the average pretest score of 3.41 and posttest score of 7.94, resulting in an N-gain value of 0.68, which falls into the medium category. Group analysis showed that all four groups, each performing three experiments across three meetings, experienced improvement, with Group 3 achieving the highest results in the high N-gain category. These findings suggest that the implementation of the scientific-based LKPD not only facilitates students in mastering Physics concepts more deeply but also encourages activeness, collaboration, and the ability to connect experimental results with theoretical understanding. Therefore, the developed LKPD is considered feasible as an alternative teaching material, capable of enhancing learning motivation and improving student learning outcomes on Newton’s Laws.   Keywords: LKPD, scientific approach, learning motivation, learning outcomes, Newton's Laws